Dinamika Pengelolaan Desa Wisata Lumbung Stroberi di Kota Batu Jawa Timur - Soedarso; Adi Suryani; Zainul Muhibbin; Moh Saifulloh (Faculty of Social and Political Science, 2022)
Tourism as one of the important sectors supporting the improvement of community welfare has experienced obstacles during the COVID-19 pandemic. The COVID-19 pandemic, which has not yet been fully completed, presents its own challenges for the management of a tourist village. This article discusses how the development of the importance of natural tourism trends in general, as well as tourist villages, especially Strawberry Barn tourism in Batu City. The data search method is through interviews and secondary data. Lumbung Strawberry Tourism, which was established in 2018, with the support of various parties, has managed to survive the COVID-19 pandemic by developing an online business; and by continuing to reopen tourist destinations after entering the new normal period in 2021 until now.